Energy market deregulation: A new perspective on dividend smoothing - Balli F; Balli HO; Hoxha I; Nguyen H; Dang THN (Elsevier B.V. Netherlands, 2026)
This paper investigates how U.S. electricity and gas utility firms adapted their dividend policies in response to deregulation of the energy sector, with a focus on understanding the internal financial mechanisms that support or constrain dividend smoothing. Using Lintner’s (1956) speed of adjustment model and a variance decomposition framework, we provide new evidence that deregulation significantly reduced dividend smoothing among utility firms, unlike their counterparts in the broader energy sector or non-energy industries. Specifically, we find that after deregulation, utility firms relied more heavily on debt financing and curtailed investment when faced with an income shock but also reflected that shock in the dividends more than before deregulation. Our empirical analysis draws on firm-level data from 1969 to 2021 and compares behaviour before and after deregulation across multiple firm categories, including a matched sample of non-utility firms. We show that deregulation made it harder for firms to maintaining the same level of dividend smoothing. These findings give insights on the importance of regulatory context in corporate finance research, and how market liberalization can impact not only competition and pricing for the affected sectors, but also the strategies firms use to balance investor expectations and operational needs.
Keywords: Energy sector deregulation; Dividend smoothing; Corporate financial policy; Market liberalization; Financial stability; Comparative financial systems; International Financial Markets